Smart City Sustainability Disclosure: Local Government Digital Legitimacy in Indonesia - Wahyu Mustika Rani; Sri Pujiningsih; Satia Nur Maharani (IQTISHODUNA, 2026)
Digital transformation has encouraged city governments in Indonesia to adopt the concept of smart cities as an effort to improve public services while strengthening accountability for sustainability. Smart city websites now serve not only as a medium for information, but also as an instrument of legitimacy for local governments to demonstrate their environmental responsibility. This study aims to analyze patterns of environmental sustainability disclosure on smart city websites in Indonesia through a thematic approach covering five main categories: environmental commitment, management transparency, real environmental programs, public participation and education, and symbols of representation. This study uses a qualitative approach with content analysis methods. Data were collected from 24 district-level smart city websites.cities included in the first phase of the national program “Movement Towards 100 Smart Cities”.The analysis results show that the most dominant disclosures are in the categories of environmental commitment and real programs, while transparency and public participation are still limited. These findings indicate that local governments use websites as a means of non-financial reporting to build public legitimacy through sustainability narratives. From an accounting perspective, this pattern confirms the function of digital sustainability disclosure as a form of environmental accountability and institutional legitimacy in the era of digital governance.